PENERAPAN METODE IQRA’ DALAM PEMBELAJARAN AL-QUR’AN BAGI LANSIA DI MAJELIS TAKLIM HUMAIRAH PIRUKO KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - Gustina Maharani; Arman Husni; Iswantir M; Salmi Wati (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated in the teaching and learning process, the teacher uses the lecture method, although it is rarely applied by the teacher in the teaching and learning process, it's just that the teacher is more often in making summaries and giving assignments to students. The teacher has made efforts or methods in the learning process even though not all of them have been implemented by the teacher, the goal is that students are motivated in learning, but in fact there are still some things that researchers found, it can be seen from the lack of student interest in learning fiqh, students do not do the tasks given by the teacher , and students pay less attention when the teacher explains the material when learning takes place, some talk to their classmates, or do other things that can interfere with learning concentration. Therefore, to achieve success they need the spirit and motivation of a teacher. As for the author's goal in this study is to determine the efforts of teachers in increasing student motivation in learning Fiqh Class VII. This type of research is a descriptive qualitative research, which is a method that describes the situation that occurs in the field systematically. Sources of data in this study were teachers who taught Fiqh in class VII as key informants, while the supporting informants in this study were class VII students of MTsN 3 Agam Balingka. To collect data, the authors conducted observations, interviews and documentation, as well as to measure the validity of the data using something else by comparing the data obtained from the observation data and the results of interviews with the research object. From the research that has been done, it can be concluded that the teacher's efforts in increasing student learning motivation in class VII Fiqh learning at MTsN 3 Agam Balingka are less than optimal due to the teacher's efforts to increase students' motivation in learning Fiqh Class VII is only by giving numbers, giving tests, know learning outcomes, and praise. While the teacher has not implemented the provision of prizes, competition or competition, ego-involvement and punishment. Keywords: Muraja'ah Method, Memorizing the Qur'an, PBQ Santri at PPM Diniyyah PasiaTeacher's Efforts, Increasing Learning Motivation